(untitled) - Krantz, William B. (Hoboken, N.J., 2007)
This book is unique as the first effort to expound on the subject of systematic scaling analysis. Not written for a specific discipline, the book targets any reader interested in transport phenomena and reaction processes. The book is logically divided into chapters on the use of systematic scaling analysis in fluid dynamics, heat transfer, mass transfer, and reaction processes. An integrating chapter is included that considers more complex problems involving combined transport phenomena. Each chapter includes several problems that are explained in considerable detail. These are followed by several worked examples for which the general outline for the scaling is given. Each chapter also includes many practice problems.
Keywords: Transport theory,Chemical reactions,Scaling laws (Statistical physics),Approximation theory,Measurement,Lý thuyết vận chuyển,phản ứng hóa học,Thang đo pháp luật (thống kê vật lý),Lý thuyết xấp xỉ,Sự đo lường